Improvement of the superconducting properties of polycrystalline FeSe by silver addition. (6th November 2015) - Nazarova, E; Balchev, N; Nenkov, K; Buchkov, K; Kovacheva, D; Zahariev, A; Fuchs, G
Abstract: We investigated the influence of different Ag additions (up to 10 wt%) on the superconducting properties of FeSe0.94 . The structural investigations (XRD and SEM) indicated that Ag is present in three different forms. Ag at grain boundaries supports the excellent intergrain connections and reduces Δ T to values smaller than 1 K at B = 0 and Δ T ≤ 2.74 K at B = 14 T. Ag insertion in the crystal lattice unit cell provides additional carriers and changes the electron–hole imbalance in FeSe0.94 . This results in an increase in the magnetoresistive effect (MR) and critical temperature ( T c ). Reacted Ag forms a small amount (∼1%) of Ag2 Se impurity phase, which may increase the pinning energy in comparison with that of the undoped sample. The enhanced upper critical field ( B c2 ) is also a result of the increased impurity scattering. Thus, unlike cuprates, Ag addition enhances the T c, B c2, pinning energy and MR making the properties of polycrystalline FeSe0.94 similar to those of single crystals.